Kejelasan Sasaran Anggaran, Sistem Pelaporan dan Kompetensi Perangkat Desa pada Akuntabilitas Pengelolaan Dana Desa - Sawitri, Putu Ika; Gayatri, Gayatri (E-Jurnal Akuntansi, 2021)
The purpose of this study was to determine the effect of clarity on budget targets, reporting systems and the competence in  accountability of village fund management. This research was conducted on 27 villages in Denpasar City.  Respondents in this study was 135 people with a purposive sampling method. Data collection was carried out using a questionnaire. The analysis technique used is multiple linear regression. Based on the research results, it shows that the clarity of budget targets, the reporting system and the competence of village officials have a positive and significant effect on the accountability of village fund management . Keywords: Budget; Reporting; Competence; Accountability.